Deaf Mothers: Communication, Activism, and the Family - Cheryl Najarian Souza (Disability Studies Quarterly, 2010)
This article examines the mothering experiences of college educated Deaf women and connects this to their identities as part of the Deaf community. Using feminist life history interviews with ten Deaf women, the analysis focuses on their work as mothers and the connections with "maternal thinking," difference, and sameness. Findings include an analysis of the various strategies that these mothers used in their mothering, which include teaching the skills of lifetime educators and self-advocates to deaf children, sending their hearing children to Kids of Deaf Adults (KODA) camps and incorporating their activism and volunteering in their mothering. The author argues that an analysis of ability along with gender is useful to further current theorizing about gender and mothering as a kind of work and that an analysis of the role of language allows us to question the idea that mothering is an innate quality of women. Instead, the author argues that, due to the social context of their life situations, "maternal thinking" and language choice are learned practices that these women negotiate in their work as mothers.
Keywords: Deaf women; mothering; gender; communication